2005
DOI: 10.1262/jrd.16068
|View full text |Cite
|
Sign up to set email alerts
|

Fine Surface Structure of Bovine Acrosome-Intact and Reacted Spermatozoa Observed by Atomic Force Microscopy

Abstract: Abstract. The atomic force microscope (AFM) provides nanometer resolution, topographic data of the natural surface structure of materials. We studied the topology of the surface structure of bovine sperm heads during the acrosome reaction by AFM. In addition, we numerically analyzed the areas of the median sagittal plane of the sperm heads. Bovine frozen-thawed spermatozoa were washed, capacitated by heparin, and incubated with lysophosphatidylcholine (LPC) to induce the acrosome reaction, smeared on a cover g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Studies using AFM images identified differences between sperm with intact acrosome and reacted acrosome [20], [21]. The area of the anterior portion of the sperm head with reacted acrosome was approximately 40% smaller than that of sperm with intact acrosome [21].…”
Section: Discussionmentioning
confidence: 97%
“…Studies using AFM images identified differences between sperm with intact acrosome and reacted acrosome [20], [21]. The area of the anterior portion of the sperm head with reacted acrosome was approximately 40% smaller than that of sperm with intact acrosome [21].…”
Section: Discussionmentioning
confidence: 97%
“…For comparison, the head of human sperm imaged by AFM looks almost circular with longitudinal and transverse profiles of about 5.2 and 4.1 lm, respectively (Joshi et al 2001b). AFM images show that the head of bovine spermatozoa is 9 lm long, 4 lm wide, and 0.4 lm thick (Saeki et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, AFM is the only technique capable of imaging the surface of living cells at nanometer scale almost in real time (Berdyyeva et al, 2005;Jalili and Laxminarayana, 2004;Shao et al, 1996) without the need for special sample preparation and/or fixation. AFM has been applied for determining the structural and topological features of human (Joshi et al, 2000;Joshi et al, 2001a,b;Kumar et al, 2005Kumar et al, , 2006, bovine, ram, boar, goat, and mouse (Allen et al, 1995;Ellis et al, 2002;Saeki et al, 2005) spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study by Takano et al (2004) provides the details of surface structure changes in spermatozoa from mouse epididymis associated with maturation [13]. Saeki et al (2004) have provided similar details about sperm head including acrosome, equatorial segment, post acrosomal region and neck during acrosome reaction induced by lysophosphatidylcholine are given [14]. In addition, a numerical analysis carried out by the research group indicates that the area of medial sagittal plane of the anterior portions of acrosome-reacted sperm heads is approximately 40% less than those of intact heads.…”
Section: Morphological and Pathological Changes Of Spermatozoamentioning
confidence: 99%